Introducing the POPVESL Score for Intrarenal Vascular Complications of Percutaneous Nephrolithotomy: Experience from a Single high-volume Referral Center - Shadpour, Pejman; Yousefzadeh Kandevani, Naser; Maghsoudi, Robab; Etemadian, Masoud; Abian, Nasrollah (Urology Journal, 2020)
Purpose: Percutaneous-nephrolithotomy (PCNL), is the current modality of choice for large renal stones. Delayed post-op bleeding may herald pseudo aneurysm (PA) or arteriovenous fistula (AVF) necessitating costly and inconsistently available angioembolization, or prolonged hospitalization. The goal of this study is to identify criteria that may predict response to conservative therapy, for delayed bleeding from post PCNL intrarenal vascular lesions. Materials and methods: We reviewed all data on patients re-admitted for post PCNL gross hematuria at our high volume center between 2011 and 2016. Perioperative findings, factors related to the stone and management details, were subjected to multifactorial analysis. Logistic regression for multivariable analysis and ROC curves to find thresholds predicting mandatory angioembolization. Results: Of 4403 PCNLs, 83 (1.9%) with delayed bleeding were diagnosed with intrarenal vascular lesions: Arteriovenous fistulas in 54 (AVF, 65%) and pseudoaneurysm in 29 (PA, 35%). Overall 49 (59%) responded to conservative management but 34 (41%) eventually required angioembolization. On multivariable analysis, predictive factors for poor response to conservative treatment were requiring transfusion beyond initial stabilization, pseudoaneurysm, history of open renal surgery, longer interval-to-second-admission, and size of vascular lesion. The proposed POPVESL score (short for Post PNL Vascular Embolization selection) when below 11, correctly predicts success of conservative management with 81.6% sensitivity & 100% specificity. Conclusion: Our findings including the proposed POPVESL score have the potential for clinical application and enhancing practical guidelines on the management of post-PCNL bleeding.